PSYCHOLOGICAL RESILIENCE AND ORGANIZATIONAL COMMITMENT: THE NIGERIAN EXPERIENCE - B. M. Nwibere; G. O. Worlu (Scholars Digest Publishing, 2023)
This study empirically investigated the relationship between psychological resilience and organisational commitment. The sample comprised two hundred eighty (280) managerial and non-managerial employees from seven major oil companies in the Niger Delta Region of Nigeria. The research employed a quasi-experimental design, deemed most suitable for administrative sciences. Both primary and secondary data were utilized. The Spearman rank correlation coefficient was employed for data analysis using the Statistical Package for Social Sciences (SPSS) version 25. The findings revealed a positive and significant relationship between employees' psychological resilience and organisational commitment. Specifically, dimensions of psychological resilience, including organisational adaptation, organisational resourcefulness, and organisational learning, were found to significantly influence various facets of organisational commitment, including affective, normative, and continuance commitment. Based on these findings, it was concluded that employees' psychological resilience enhances their commitment to the organisation within the Nigerian oil and gas industry. In light of these results, it is imperative for managers in Nigeria's oil and gas sector to effectively manage employees' resilience to foster organisational commitment. Additional practical implications for managing employees' resilience in the workplace are discussed.